2009
DOI: 10.1055/s-0029-1241208
|View full text |Cite
|
Sign up to set email alerts
|

Kinematical Profiling of the Front Crawl Start

Abstract: This study analysed the start phases of 15 elite front crawl swimmers, all specialists of sprint events. The first aim was to determine which phases were correlated with the 15-m start time. The features common to the sample of swimmers were then established and individual profiles were clustered. The subjects performed two 25-m trials at the 50-m race-pace using their preferential start technique (grab start). The kinematical analysis assessed the durations of the block, flight, entry, glide, leg kicking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
65
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 10 publications
9
65
1
9
Order By: Relevance
“…Interestingly, they also obtained faster underwater turn velocities in all events except breaststroke, even though it has been previously explained that this parameter is only important for the start performance (Burkett, Mellifont, & Mason, 2010;Cossor & Mason, 2001;Vantorre, Seifert, Fernandes, Vilas Boas, & Chollet, 2010a). Finally, they showed the ability to stabilize some of the turn parameters throughout the race compared to the lower expertise swimmers (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, they also obtained faster underwater turn velocities in all events except breaststroke, even though it has been previously explained that this parameter is only important for the start performance (Burkett, Mellifont, & Mason, 2010;Cossor & Mason, 2001;Vantorre, Seifert, Fernandes, Vilas Boas, & Chollet, 2010a). Finally, they showed the ability to stabilize some of the turn parameters throughout the race compared to the lower expertise swimmers (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 72%
“…All distances were calibrated based on the pool's marks (e.g., the 5-m and 15-m marks of the swim lanes). The parameters selected are often reported in the literature (e.g., Hubert, Silveira, Freitas, Pereira, & Roesler, 2006;Ruschel, Araùjo, Pereira, & Roesler, 2007;Vantorre et al, 2010).…”
Section: Starting Parametersmentioning
confidence: 99%
“…Hence, the start and the turn combined account to a total of 31-32% of the time (i.e., nearly one third of a 100-m race time). Studies reported the parameters that swimmers should consider to enhance their on-block (Fischer & Kibele, 2016;Tor et al, 2015;Vantorre et al, 2010) and in-water back start (de Jesus et al, 2013;Takeda, Itoi, Takagi, & Tsubakimoto, 2014). The time at the 15-m mark (main outcome) depends significantly from the takeoff velocity, entry angle, underwater time and distance (Fischer & Kibele, 2016;Vantorre, Chollet, & Seifert, 2014).…”
Section: Contribution Of Start Plus Turn To Final Race Timementioning
confidence: 99%
See 2 more Smart Citations